Experimental test bench for the study of impact of intermediate belt drive construction of belt conveyor on its operation - Goncharov K.A.; Grishin A.V. (Научно-технический вестник Брянского государственного университета)
This article describes the structure of experimental test bench for the study of impact of intermediate belt drive con-struction of belt conveyor on its operation. There is a justification for test bench designing and conducting a variety of tests using this test bench.